1999
DOI: 10.1111/1468-2427.00211
|View full text |Cite
|
Sign up to set email alerts
|

Local Growth Coalition: The Context and Implications of China’s Gradualist Urban Land Reforms

Abstract: China's urban land reforms are being implemented within a framework of general economic reforms which are gradualist in nature. Thus, the urban land reforms are moving step by step towards the establishment of a land market. This gradualism is developing in association with a redefinition of central-local intergovernmental relations in the reform era, and with the advent of localism. In this context, gradual urban land reforms have become an implicit programme to nurture local enterprises and developers, a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
185
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(186 citation statements)
references
References 13 publications
0
185
1
Order By: Relevance
“…In the process of attracting both foreign and domestic investment, urban governments tend to establish more and more DZs in the outskirts, which often lead to the agglomerated development of industrial land [57]. Along with the establishing of DZs, various scholars have confirmed that institutional changes, through land use "policies" [58] such as land use right and ownership [59], the tax-sharing reform of 1994 [60], and the housing commercialization reform [61], have great impacts on urban land expansion process in China [33].…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
“…In the process of attracting both foreign and domestic investment, urban governments tend to establish more and more DZs in the outskirts, which often lead to the agglomerated development of industrial land [57]. Along with the establishing of DZs, various scholars have confirmed that institutional changes, through land use "policies" [58] such as land use right and ownership [59], the tax-sharing reform of 1994 [60], and the housing commercialization reform [61], have great impacts on urban land expansion process in China [33].…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
“…However, thirdly, the effects of such ambiguity over property rights bear less heavily on firms (who report more confidence in the regulatory system than in other NICs) 14 than on domestic landowners/farmers, whose land may easily be taken over for 'public use' with minimal compensation (Zhang 2006). Finally, despite economic liberalisation, relations between state/official and society/businesspersons/ professional consultants remain asymmetric in political terms (Zhu 1999;Zhang 2002). The state has legitimated external interests in an attempt to unleash the economic dynamism of societal groups, but in a way that directs that power toward its own goals.…”
Section: -2 Agents and Motivationsmentioning
confidence: 99%
“…Decision makers at the city scale still need to face challenges or pressures against ecological conservation from pro-growth coalitions, which involve governmental departments and non-governmental actors. The pro-growth interest binds local bureaucracy at the scales of the city, individual districts, and streets to enterprises and inward foreign capital into an informal coalition to address regional competition and to circumvent central pressure for revenue submission (Zhu, 1999a). The demands of most of the pro-growth coalitions on converting additional land resources into local development (Zhu, 1999b) may shape pressures against ecological conservation in local decision-making.…”
Section: Resultsmentioning
confidence: 99%